An Effective Development and Analysis of a Mobile Robot - Jagannath Sahu; B.B. Choudhury; M.R. Patra (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper deals with the design of a battery operated Mobile Robot and development of various modes of its control. The Mobile Robot can be operated in three different modes, namely Dual Tone Multi Frequency (DTMF), Radio Frequency (RF) and ZigBee thereby enabling a multi- dimensional control system. The Mobile Robot is a single seated carrier. It can also be used to transport substantial amount of physical load for short distances. It is a prototype of a multi-use robot having a wide range of applicability according to the requirement after suitable modifications. Thus it can be easily applied inside a hospital to carry patients, as a wheel chair for physically challenged people, to carry goods in large shopping malls, as golf cars, can also be used for industrial purposes with adequate modifications. It can also be used as cleaning machine at railway stations, airports, museums, large halls. It uses a DC power source and not any conventional energy sources. Hence it is ecofriendly and this Mobile Robot can be termed as an advancing step in the field of battery operated vehicles.